Fragility-based methodology for evaluating the time-dependent seismic performance of post-tensioned timber frames. Issue 1 (February 2020) - Granello, Gabriele; Broccardo, Marco; Palermo, Alessandro; Pampanin, Stefano
Since 2010, the construction of post-tensioned wooden buildings (Pres-Lam) has been growing rapidly worldwide. Pres-Lam technology combines unbonded post-tensioning tendons and supplemental damping devices to provide moment capacity to beam–column, wall–foundation, or column–foundation connections. In low seismic areas, designers may choose not to provide additional damping, relying only on the post-tensioning contribution. However, post-tensioning decreases over time due to creep phenomena arising in compressed timber members. As a consequence, there is a reduction of the clamping forces between the elements. This reduction affects the seismic response of Pres-Lam buildings in the case of low- and high-intensity earthquakes. Therefore, understanding and accounting for the post-tensioning losses and their uncertainty are paramount for a robust assessment of the safety of Pres-Lam constructions. So far, however, there have been no comprehensive studies which tackle the overall seismic performance of such systems in the presence of time-varying post-tension losses and the associated uncertainty. This study tackles this research gap by introducing a comprehensive seismic evaluation of Pres-Lam systems based on time-dependent fragility curves. The proposed fragility analysis is specifically designed to account systematically for time-varying post-tension losses and the related uncertainty. The method is applied to two case studies, designed, respectively, with and without supplemental damping devices. In terms of structural performance, results show that the use of additional dissipaters mitigates the effect of post-tensioning loss for earthquakes of high intensity. Conversely, performance under low-intensity earthquakes is strongly dependent on the post-tensioning value, as the reduction of stiffness due to the anticipated rocking motion activation would lead to damage to non-structural elements.